2016
DOI: 10.1117/12.2213609
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of chorioretinal vasculature in mice in vivo using a combined OCT/SLO imaging system

Abstract: Chorioretinal blood vessel morphology in mice is of great interest to researchers studying eye disease mechanisms in animal models. Two leading retinal imaging modalities --Optical Coherence Tomography (OCT) and Scanning Laser Ophthalmoscopy (SLO) --have offered much insight into vascular morphology and blood flow. OCT "flow-contrast" methods have provided detailed mapping of vascular morphology with micrometer depth resolution, while OCT Doppler methods have enabled the measurement of local flow velocities. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…7(g) ], which has not been previously visualized in the mouse in vivo without contrast agent. 46 , 47 OCTA data sets can be used to produce very high contrast maps of retinal vasculature, as illustrated with a depth-color-coded projection of the inner retina vessels [ Fig. 7(h) ].…”
Section: Resultsmentioning
confidence: 99%
“…7(g) ], which has not been previously visualized in the mouse in vivo without contrast agent. 46 , 47 OCTA data sets can be used to produce very high contrast maps of retinal vasculature, as illustrated with a depth-color-coded projection of the inner retina vessels [ Fig. 7(h) ].…”
Section: Resultsmentioning
confidence: 99%
“… Simultaneous SLO and OCT imaging of a nude mouse with two fluorescence channels injected with fluorescein and nanoparticles tagged with rhodamine-X: (A) Image of ”green” (“GFP”) fluorescence channel; (B) Image of ”red” fluorescence channel; (C) Image of the ratio between (B) and (A); D Image of the retinal vasculature extracted from OCT (pv-OCT); (E) Image of the choroidal vasculature obtained from OCT. (F-J) x3 magnified images of the white dashed area from Figure 4 A-E respectively showing enhanced visualization of chorioretinal vasculature. ( Adapted from Goswami et al 2016 163 ). …”
Section: Figurementioning
confidence: 99%
“…Micrographs showing pv-OCT/SLO imaging showing images visualized at different layers such as nerve fiber layer (NFL), inner plexiform layer (IPL), inner nuclear layer (INL), outer plexiform layer (OPL), outer nuclear layer (ONL), inner segment (IS), outer segment (OS), retinal pigment epithelium (RPE), and choroid, respectively. ( Adapted from Goswami et al 2016 163 ).…”
Section: Figurementioning
confidence: 99%
“…Recent progress in polarization-sensitive OCT (PS-OCT), a functional extension of OCT that is capable of visualizing and quantifying melanin concentrations at the retina enabled clinicians to precisely diagnose multiple stages of AMD and has been widely employed in the research environment [4]. Moreover, there have been studies that quantified lipofuscin from the retina with autofluorescence measurement [5,6], and visualization of CC has also been conducted using a mouse model [7]. However, none of the studies reported the development of a multi-modal system that could acquire images of melanin concentration, lipofuscin accumulation and CC visualization with a single imaging system.…”
Section: Introductionmentioning
confidence: 99%